Enhancing circular economy capability in Indonesian MSMEs: The role of sustainable supply chain design in the fashion and cosmetics industries - Nindiya, Theresia Mayke; Kusumastuti, Ratih Dyah (EcoProfit: Sustainable and Environment Business, 2025)
Background: The circular economy is a potential concept for the implementation of MSMEs in Indonesia as one of the largest contributors to GDP in Indonesia. Through two of the five priority industries to implement circular economy, namely the fashion and cosmetics industries, this study aims to Analyzing the influence of supply chain relationship management on sustainable supply chain design. Then analyze the influence of sustainable supply chain design on circular economy capability of MSMEs in Indonesia. Methods: The research was conducted on 72 MSMEs in the fashion and cosmetics industry in Java and Bali, Indonesia, which have implemented at least one of the three 3R concepts (reduce, reuse, recycle). Data testing in this study used Partial Least Square - Structural Equation Modeling (PLS-SEM) as a method that is currently widely applied in many social science disciplines, including supply chain management. Findings: The results showed that supply chain relationship management has a positive effect on sustainable supply chain design in the fashion and cosmetics industry MSMEs. Furthermore, sustainable supply chain design has a positive effect on the circular economy capability of fashion and cosmetics industry MSMEs. Conclusion: In general, sustainable supply chain management can influence the circular economy capability of fashion and cosmetics industry MSMEs in Indonesia through the implementation of green supply chain management. Novelty/Originality of this article: This study fills the gap in the literature by using PLS-SEM method to validate the link between supply chain relationship management and circular economy capability, which is still rarely applied to the MSME sector, especially in Indonesia.